NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI PISOMBO MASYARAKAT BUTON DI KABUPATEN SERAM BAGIAN BARAT - Manahaji, La Amu; Umarella, Samad; H Rajab; Rustina N. (Jurnal Studi Islam, 2025)
Abstract: This research is about Islamic education values in Pisombo tradition in Tonu Jaya village, West Seram district, Maluku. Pisombo is a tradition of celebrating the transition of a Buton girl to her adulthood. Pisombo tradition is also known by other terms, such as Posuo, Bakurung, and Pingitan. In practice, Pisombo is carried out by placing the girl involved in this tradition in a separate room for 4 or 8 days without being able to have contact with anyone other than Maebiang, who serves as the girl’s guide during the Pisombo procession with family and other people. The research intends to describe the Pisombo procession and reveal the Islamic education values contained therein. The aim is to emphasize that the values of Islamic education must be maintained in the Pisombo tradition so that the label as an Islamic tradition remains attached to it. This research is qualitative, relying on primary data sources in the form of interviews with traditional, community, and religious leaders, while secondary data are books, research articles, and other written sources related to Pisombo. The research found that the Pisombo tradition is full of Islamic values, such as the value of belief education, worship, child education, and brotherhood education. These values should be maintained in the Pisombo tradition. Key words: Pisombo, Buton Society, Islamic Education Values, Tradition